DEVELOPMENT OF CONSTRUCTION PARAMETERS OF ROLLER MECHANISMS WITH BELT CONVEYOR STRUCTURES - Abdurakhmanova , Muattar; Umirzoqova , Barchinoy (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This article presents the development of constructive parameters of roller mechanisms with elastic elements for belt conveyors. The interaction between rollers and elastic components and their influence on load distribution are analyzed. Optimal geometric and technical parameters are determined to improve the efficiency of the mechanism. The proposed design enhances the reliability and durability of conveyor systems. The obtained results are recommended for industrial application.